1998
DOI: 10.1128/aem.64.10.3878-3881.1998
|View full text |Cite
|
Sign up to set email alerts
|

Stereo- and Regioselective Hydroxylation of α-Ionone by Streptomyces Strains

Abstract: A total of 215 Streptomyces strains were screened for their capacity to regio- and stereoselectively hydroxylate β- and/or α-ionone to the respective 3-hydroxy derivatives. With β-ionone as the substrate, 15 strains showed little conversion to 4-hydroxy- and none showed conversion to the 3-hydroxy product as desired. Among these 15 Streptomyces strains, S. fradiae Tü27, S. arenae Tü 495, S. griseus ATCC 13273, S. violaceoniger Tü 38, and S. antibioticus Tü 4 and Tü 46 converted α-ionone to 3-hydroxy-α-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 18 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…Microbial oxidative biotransformations of and -ionones have been reported using different bacteria including Streptomyces. 21 P450 enzymes from S. griseolus and S. griseus were shown to oxidise and -ionone at the allylic C3 and C4 positions, respectively. 47 Variants of the self-sufficient cytochrome P450, P450Bm3, are able to selectively oxidise -ionone at the allylic C4 position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial oxidative biotransformations of and -ionones have been reported using different bacteria including Streptomyces. 21 P450 enzymes from S. griseolus and S. griseus were shown to oxidise and -ionone at the allylic C3 and C4 positions, respectively. 47 Variants of the self-sufficient cytochrome P450, P450Bm3, are able to selectively oxidise -ionone at the allylic C4 position.…”
Section: Discussionmentioning
confidence: 99%
“…CYP101B1 has little sequence similarity with its closest structurally characterised relative outside of the CYP101 family, CYP176A1 (P450cin) or other ionone binding P450 monooxygenases such as CYP109D1 and CYP264B1, or those from Streptomyces species which are known to oxidise norisoprenoids (Table S1, vide infra). [20][21][22][23] Despite the relatively low sequence similarity with CYP101B2 from N. tardaugens a comparison of the residues that are likely to make up the active site and substrate access channel revealed the almost complete conservation of amino acids ( Fig. 1 and Table S2).…”
Section: Phylogenetic Analysis Of Cyp101b1mentioning
confidence: 99%
“…The microbial biotransformation of racemic α‐ionone using different Streptomyces strains,19 fungi such as Aspergillus niger, 20 immobilized cells of Nicotium tabacum, 21 and cultured cells of Caragana chamlagu 22 has been reported. Moreover, different bacterial P450s from Bacillus subtillus, Sorangium cellulosum, Novaspinghobium aromaticivorans and Streptomyces have been shown to hydroxylate α‐ionone 2327.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different bacterial P450s from Bacillus subtillus, Sorangium cellulosum, Novaspinghobium aromaticivorans and Streptomyces have been shown to hydroxylate α‐ionone 2327. In most of the biotransformation studies of racemic α‐ionone that have been reported so far, trans ‐3‐hydroxy‐α‐ionone was found to be the main product 19,23,25. Other studies reported the formation of 2 diastereomers of 3‐hydroxy‐α‐ionone from racemic α‐ionone hydroxylation 17,27.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ionones and their derivatives are important starting materials for the synthesis of several natural products and important intermediates in the metabolism of terpenoids, for example, in carotenoid biosynthesis [11], and have been isolated from many sources [12]. Ionone derivatives have also different biologically activity [13–17].…”
Section: Introductionmentioning
confidence: 99%